Desenvolvimento e caracterização de cristais de K2GdF5, LaAlO3 e Al2O3 para aplicação em dosimetria das radiações e imagens digitais termoluminescentes para campos de radiação de nêutrons, ultravioleta, X e gama - Edna Carla da Silva (2014)
In this work, thermoluminescent (TL) materials were developed and characterized aiming applications in dosimetry for X, gamma, neutron and ultraviolet radiation fields. Micro and nanosized aluminum oxide (Al2O3) polycrystals in the alpha phase were doped with different carbon atoms concentrations and sintered at 1700 °C, 1745 °C and 1770 °C. Samples of - Al2O3 doped with 1.0 and 5.0 at.% of carbon and sintered at 1745 °C have shown excellent TL responses for gamma doses concerning to its reproducibility and linearity. K2GdF5 single crystals doped with 0.2, 1.0, 5.0 and 10.0 at.% of trivalent optically active Dy3+ ions have been synthesized under hydrothermal conditions and characterized for thermal neutron fields. K2Gd0.95Dy0.05F5 crystals have shown TL output for thermal neutrons (15,000 a.u.) well above that obtained in a previous work for fast neutrons (707 a.u.) and gamma radiation (15 a.u.). Their main TL emission peaks are centered at 230 °C for thermal neutrons and at 215 °C for fast neutrons. This good performance is attributed to the high capture cross section for thermal neutrons of 155Gd and 157Gd isotopes, which are present in amounts of 14.7 and 15.7% in natural Gadolinium. Undoped LaAlO3 single crystals and those doped with 1.0 and 5.0 at.% of Ce3+ as well as those co-doped with 5.0 at.% of Ce3+ and 1.0 at.% of Dy3+ were characterized for use in UV dosimetry. The LaAlO3 single crystals co-doped with 5.0 at.% of Ce3+ and 1.0 at.% of Dy3+ and sensitized with 147.6 mJ.cm-2 of UV radiation have shown high TL sensitivity, with TL emission peaks centered at 125.7 °C, 151.2 °C, 213.1 °C e 287.2 °C. The possibility of using these three materials in digital radiography have been evaluated for X, gamma, UV and neutron radiation fields. The thermoluminescent films manufactured using microsized -Al2O3 doped with 1.0 and 5.0 at.% of carbon have presented the best images for X-rays fields, with good resolution and profundity. UV sensitized films of LaAlO3 single crystals co-doped with Ce3+ and Dy3+ were manufactured. TL images with good resolution were obtained for UV fields. On the other hand, for neutrongraphy applications, the TL film made with K2Gd0.95Dy0.05F5 crystals was irradiated with 10 mSv of thermal neutrons. This very low neutron dose has produced no TL output in the TL film. However, after being irradiated with 50 Gy of gamma dose, it was possible to capture a not satisfactory TL image. Taking into account the high TL output of this material to thermal neutrons, when compared to its TL output for gamma radiation, we may infer that, for higher thermal neutron doses, this material could be investigated in future work for applications in neutron digital imaging.